Analysis of moisture migration, temperature, and pore structure characteristics of the muddy clay column subject to artificial ground freezing based on LF NMR - Zhou, Jie; Zhou, Huade; Wang, Chuanhe; Guo, Zhongqiu; Pei, Wansheng (Tunnelling and underground space technology, 2023)
•The temperature characteristics along the muddy clay column are analyzed with moisture migration.•Moisture migration along large column during F-T process is discussed by NMR scanning results.•Pore size distribution along muddy clay column during F-T process is determined.•The coupling mechanism between moisture migration, temperature, and pore structure of clay is inferred. Nowadays, artificial ground freezing (AGF) is widely used in the construction of underground spaces in soft soil areas. Most of the existing studies are focused on micro and macro analyses of small volume samples under AGF, while the research on large soil column is insufficient. Therefore, it’s crucial to explore the characteristics of the large soil column by AGF. In this paper, the low field nuclear magnetic resonance (LF NMR), and the unidirectional freezing test of large muddy clay columns were carried out. The results indicate that the most difference is that along the soil column, each soil layer has a connection with each other, owing to the pore structure connectivity and moisture migration within it. Moreover, slow-growing platforms or even temperature crosses appeared during thawing, due to the downward movement of water under consolidation and gravity which may interfere with heat transfer (upward movement). Along the large muddy clay column, moisture migration in the soil column is coupled with temperature as well as pore structure. Specifically, temperature difference and pore structure provide the power source and transport channel for moisture migration, respectively, while the moisture migration changes the temperature of each layer of the soil column and the composition of the pore structure. The pore structure indirectly influences the temperature of soil column by affecting the amount of moisture migration, while temperature significantly changes the number and size of pores inside the soil column. Furthermore, by LF NMR experiments, it was found that the pore size distribution was relatively dispersed and the characteristics of moisture migration at different heights of the soil column could be divided into three stages. This study can be used as theoretical guidance for understanding the change laws among moisture migration, temperature, and pore structure of the muddy clay as well as for helping the construction of AGF in the underground space.